Pocket guide to diagnostic tests / Diana Nicoll [and three others] - Nicoll, Diana; Mark Lu, Chuanyi; Pignonr, Michael; McPhee, Stephen J. (New York : McGraw-Hill [distributor], 2012)
A quick reference guide to the selection and interpretation of more than 450 commonly used diagnostic tests.
Previous ed.: 2008.
Keywords: Clinical Laboratory Techniques -- Handbooks; Diagnosis, Differential -- handbooks; Diagnostic Imaging -- Handbooks; Diagnostics biologiques -- Guides, manuels, etc; Diagnosis, Laboratory; Handbooks, manuals, etc